IMPROVING STUDENTS' CRITICAL THINKING SKILLS THROUGH ARGUMENT MAPPING-BASED GUIDED INQUIRY ON HUMAN EXCRETORY SYSTEM - Muhammad Jamhari Darhany (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2020)
This study aims to analyze the improvement of students’ critical thinking skills in the features of focus, supporting reasons, reasoning, organization, conventions and integration through the implementation of argument mapping-based guided inquiry learning models. Type of this research is classroom action research, a systematic inquiry with the goal of informing practice in particular situation which adopted Kemmis and McTaggart’s models which follows the cycle of planning, action, observation and reflection. It was conducted in class XI-Avenzoar of SMA Unggulan CT Foundation Deli Serdang in the academic year 2019/2020. The sampling technique was done by total sampling consisting of 24 students with a composition of 6 boys and 18 girls. The instrument used the essay tests adapted from Finken based on Illinois Critical Thinking Essay Test and argument mapping based on van Gelder on the concept of human excretory system. The data collection methods were included the interview, observation and documentation. The whole data was employed by descriptive analysis developed by Miles and Huberman which includes three concurrent activities, data reduction, data presentation and conclusion drawing. The results showed that the features of focus and reasoning from critical thinking skills tests in Cycle I obtained the highest score of all, while the features of supporting reasons and conventions obtained the lowest score and showed no improvement at all. Meanwhile in Cycle II, the features of focus and reasoning increased significantly and obtained the highest score as well. However, the feature of supporting reasons increased simultaneously but conventions still remained. It definitely showed that there was a significant improvement between groups in Cycle I (65.42) and Cycle II (80.21) from the average score of students’ critical thinking skills through their argument mapping grading. The aspects of argument mapping, such as claims, reasons, objections, rebuttals and debates improved well between these cycles. It was strongly suggested that argument mapping could enhance students’ critical thinking skills in Biology. From the results and discussion, it could be concluded that the implementation of the argument mapping-based guided inquiry learning models on the concept of human excretory system had a very positive and significant improvement on students’ critical thinking skills. The students’ critical thinking skills were in the high category.